In situ hybridization of bat chromosomes with human (TTAGGG)n probe, after previous digestion with Alu I - Faria, Karina de Cassia [UNESP]; Morielle-Versute, Eliana [UNESP] (Sociedade Brasileira de Genética, 2002)
The purpose of this work was to verify the ability of the enzyme Alu I to cleave and/or remove satellite DNA sequences from heterochromatic regions in chromosomes of bats, by identifying the occurrence of modifications in the pattern of fluorescence in situ hybridization with telomeric DNA. The localization and fluorescence intensity of the telomeric DNA sites of the Alu-digested and undigested chromosomes of species Eumops glaucinus, Carollia perspicillata, and Platyrrhinus lineatus were analyzed. Telomeric sequences were detected at the termini of chromosomes of all three species, although, in C. perspicillata, the signals were very faint or absent in most chromosomes. This finding was interpreted as being due to a reduced number of copies of the telomeric repeat, resulting from extensive telomeric association and/or rearrangements undergone by the chromosomes of Carollia. Fluorescent signals were also observed in centromeric and pericentromeric regions in several two-arm chromosomes of E. glaucinus and C. perspicillata. In E. glaucinus and P. lineatus, some interstitial and terminal telomeric sites were observed to be in association with regions of constitutive heterochromatin and ribosomal DNA (NORs). After digestion, these telomeric sites showed a significant decrease in signal intensity, indicating that enzyme Alu I cleaves and/or removes part of the satellite DNA present in these regions. These results suggest that the telomeric sequence is a component of the heterochromatin, and that the C-band- positive regions of bat chromosomes have a different DNA composition.
Keywords: AluI; Fish; Chiroptera; telomeric sites; DAPI